Asuhan Keperawatan Pada Ny.R Tentang Pemberian Seduhan Bawang Putih Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Lansia Di Desa Naumbai - Nalisa, Feni; Safitri, Yenny; Murlianis, Murlianis (Jurnal Spektrum Kesehatan Indonesia, 2025)
Hypertension in the elderly is defined as systolic pressure above 160 mmHg and diastolic pressure above 90 mmHg. There are several risk factors for hypertension, such as age, gender, smoking, and a sedentary lifestyle that can lead to obesity. Signs and symptoms that are often found in people with hypertension are headaches, dizziness, and a heavy neck. The non-pharmacological intervention that can be done is by giving Garlic Tea. The natural content of garlic contains very important chemical compounds, one of which is volatile oil (0.1-0.36%) containing sulfur, including alliin, ajoene and vinyldithiines which are produced non-enzymatically from allicin which can thin the blood and play a role in regulating blood pressure so that it can smooth blood circulation. This study was conducted on June 9-11, 2022, then analyzing the data and carrying out interventions from the diagnosis obtained. The nursing diagnosis that emerged was Acute pain related to physical injury agents (Excessive physical exercise, sleep pattern disorders related to environmental obstacles (noise). Garlic infusion was given for 3 consecutive days and given once a day. Nursing problems can be resolved because the patient said that her blood pressure had dropped and the patient could return to her activities. Giving garlic infusion has a positive impact on the patient so that it can reduce blood pressure in Mrs. R with hypertension. It is expected that the client will always be able to pay attention to her health, to continue to consume garlic infusion regularly when blood pressure starts to rise, consume low-salt foods and pay attention to her sleep time and patterns.